POLITIK, AGAMA DAN NEGARA: PEMERINTAHAN ISLAM DI MALAYSIA - Wekke, Ismail Suardi (Millah: Journal of Religious Studies, 2016)
Mainstream discourse always separate on religion and state. In addition, this perspective arouses when there was a conflict between church and government ruler in the past. Therefore, it is a need to explore in the Muslim country how the relation between religions in this context is Islam and the state on the other side. This research was conducted in Malaysia to discover implementation of Islam as spirits of government in realizing their dream as nation. Qualitative research approach employed to discover data. In-depth interview and observation were employed in collecting data. During interview and observation, guidelines were utilized as instrument. This study shows that Islam is maintain the character of government official since the state was founded. Moreover, in the time of governing they extend the religion principle to enhance the administration activities. Finally, this research concludes that Islam and nation can coexist to expand the organization in politics.